2017
DOI: 10.1021/acs.inorgchem.7b00708
|View full text |Cite
|
Sign up to set email alerts
|

Organoimido-Polyoxometalate Nonlinear Optical Chromophores: A Structural, Spectroscopic, and Computational Study

Abstract: Ten organoimido polyoxometalate (POM)-based chromophores have been synthesized and studied by hyper-Rayleigh scattering (HRS), Stark and Resonance Raman spectroscopies, and density functional theory (DFT) calculations. HRS β values for chromophores with resonance electron donors are significant (up to 139 × 10 esu, ∼5 times greater than that of the DAS cation), but systems with no donor, or the -NO acceptor show no activity, in some cases, despite large DFT-predicted β-values. In active systems with short (phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 98 publications
4
43
1
Order By: Relevance
“…photoluminescence diagram of complex I, with the excitation spectrum shown with dashed lines and the emission spectra shown with solid lines.was found previously(Hermosilla-Ibá ñ ez et al, 2019;Lv et al, 2012;Al-Yasari et al, 2017).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…photoluminescence diagram of complex I, with the excitation spectrum shown with dashed lines and the emission spectra shown with solid lines.was found previously(Hermosilla-Ibá ñ ez et al, 2019;Lv et al, 2012;Al-Yasari et al, 2017).…”
supporting
confidence: 70%
“…There is no evidence that the [Mo 6 O 19 ] 2Àanions have any effect on the structure of the TCPP unit. To our knowledge, generally, a saddle structure is observed if no metal ions coordinate to TCPP(Diskin-Posner et al, 2000;Al- Yasari et al, 2017). If coordination occurs, a planar structure is observed…”
mentioning
confidence: 93%
“…Al-Yasari et al designed a series of organoimido POM-based dipolar chromophores and the relationship between structure and NLO properties was clarified through calculations and experiments. [193] It was revealed that although imido-POM is an unusually efficient acceptor there is no NLO response in the absence of a resonant electron donors. Compared with organic analogs, however, in the presence of a resonance donor and a short π-bridge, the imino-POM acceptor extends the charge transfer onto the POM, thereby increasing the dipole moment and thus the NLO response.…”
Section: Organic/inorganic Hybrid Porous Materials For Third-order Nlomentioning
confidence: 99%
“…The functionalization of this compound with organo-imido fragments has a general formula [Mo 6 O (19−x) (N-R) x ] 2− , where x = 1–6 and N-R is an organic unit derived from a isocyanate or a primary amine molecule bonded to a molybdenum centre [7,8,9]. This functionalization permits to obtain and design new organic-inorganic hybrid systems where the electronic properties can be modulated depending on the nature of the incorporated organic fragment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Five aliphatically-functionalized hexamolybdates were taken from the literature [21]. Seven aromatic systems with different electron donating and withdrawing abilities were also taken from the literature [10,22,23]. For the spectroscopic study, some molecules being the most representative systems were used.…”
Section: Introductionmentioning
confidence: 99%